INCREASED CARBON LOSS VIA ROOT RESPIRATION AND IMPAIRED ROOT MORPHOLOGY UNDER FREE-AIR OZONE ENRICHMENT ADVERSELY AFFECT RICE (ORYZA SATIVA L.) PRODUCTION. (7th May 2018) - KOU, T. J.; LAI, L. K.; LAM, S. K.; CHEN, D.; HE, J.
SUMMARY: The increasing tropospheric ozone concentration [O3 ] strongly affects plant growth. However, the response of belowground processes in rice ( Oryza sativa L.) systems to higher O3 is not well understood. The grain production, belowground biomass partitioning, root morphology and activity of rice (cv. Shanyou 63) were investigated in a free-air O3 enrichment platform at four key growth stages. Elevated O3 (EO3, 50% above the ambient O3 ) significantly decreased the grain yield and total biomass at the grain milky mature stage, root biomass at the tillering stage and root to shoot ratios (RRS) at the flowering and grain filling stages. The effects of EO3 on root morphology and activity varied among rice growth stage. EO3 significantly decreased root length, density, area, diameter and volume at the flowering stage, but EO3 significantly decreased various root morphological indices at the tillering, grain filling and milky mature stages. EO3 significantly increased the specific root respiration rate (root activity) and root respiration rate (autotrophic respiration) at grain filling and milky mature stages. Higher root autotrophic respiration and lower RRS in response to EO3 would reduce allocation of assimilated carbon to root growth, adversely affecting rice productivity. Our findings are critical for understanding the O3 -induced impairment of belowground processes and carbon cycling in rice cropping systems and breeding of O3 -tolerant cultivars under higher [O3 ] scenarios.